Analisis Kelayakan Usahatani Padi di Kecamatan Cawas Kabupaten Klaten - Efi Nikmatu Sholihah; S Sumarmi; Benhar Aslam (Fapetrik-UMPAR, 2022)
Rice is a staple food that is difficult to replace with other alternative foods. This makes the level of rice consumption in Indonesia quite high. Land use in Cawas District has shifted a lot to settlements and the area of ??land use for agriculture is decreasing. This indirectly implies that most of the farmers in Cawas Sub-district have shifted their land use from agricultural land to residential land because the previous farming no longer provides a profit. Farm income can be used as an indicator of farmer welfare, the higher the net income received by farmers, the higher the economic welfare level of farmers. In this regard, it is necessary to further analyze the level of use of costs, revenues, income, and the feasibility of farming so that it is known to what extent rice farming can guarantee the economic welfare of farmers' households. This research was conducted by interview method with the Mugi Subur farmer group in Cawas District and was carried out in March. Farming income analysis can be done by conducting interviews regarding the use of farming costs and the price of rice at harvest. Furthermore, based on the data, the Break Event Point (BEP) value, R/C ratio, and B/C ratio were calculated to determine the feasibility of farming. The results showed that rice farming in Cawas District provides benefits for farmers and is feasible to cultivate.